Melting behaviour and crystallisation kinetics of carbon-fibre-reinforced low-melting poly(aryl ether ketone) - Jan-Lukas Stüven; Sebastian Heimbs; Carsten Schmidt (Polymer Testing)
The dependence of material properties and residual stress formation on the crystallinity of thermoplastic composites necessitates detailed analyses regarding the melting behaviour and the crystallisation kinetics of employed semi-crystalline matrices as well as accurate crystallisation models. This paper investigates a novel low-melting poly(aryl ether ketone) (LM-PAEK) reinforced with carbon fibres, in the form of TC1225 unidirectional tape, based on isothermal and non-isothermal differential scanning calorimetry (DSC). It is shown that the LM-PAEK matrix features a double melting behaviour and exhibits an absolute crystallinity of roughly 18%. Kinetics parameters are derived from the DSC analyses and the applicability of selected crystallisation models for predicting the relative crystallinity is evaluated based on a comparison with the DSC data. Under isothermal conditions, the modified Hillier model and the parallel Velisaris–Seferis model yield good agreement. In contrast, a dual Nakamura model and a dual Kamal–Chu model yield merely moderate agreement under non-isothermal conditions.